P-289 KIDscore and PGT-A: Is there a relationship between the findings?. (30th June 2022) - Azambuja, R; Wingert, F; Proença, L.A; Hentschke, M.R; Badalotti-Teloken, I; Dornelles, V.C; Petracco, Á; Badalotti, M
Abstract: Study question: Is there a correlation between Preimplantation Genetic Tests (PGT) results and Embryoscope's KIDscore? Summary answer: It seems that the higher the KIDscore, the higher the percentage of euploid embryos. What is known already: Time lapse technology is bringing new perspectives in the relationship of embryos' morphokinetics and implantation rates after assisted reproduction techniques. However, it seems that only the embryo morphokinetics could be insufficient to predict euploidy. The KIDscoreTM D5 (KS5) algorithm, thus, is used for improving the implantation rates after a single euploid embryo transfer in its blastocyst stage and is related to higher rates of euploid embryos the higher the KS5, which could lead to higher implantation rates. Study design, size, duration: Retrospective, observational study performed at a reproductive medicine center, using data collected between 2019 and 2021. A total of 802 embryos were included for analysis. Participants/materials, setting, methods: All the embryos were biopsied for PGT (A, SR, and M), after being cultured for five or six days in an Embryoscope® time-lapse incubator (Vitrolife®, Canada). The embryos were then divided into three groups according to the KS5 evaluation: G1 (1-4), G2 (4.1-7), G3 (7.1-9.9) and the percentage of euploidy was evaluated in each group. For statistical analysis, Chi-square, and ANOVA tests, and Pearson correlation were used, considering p < 0.05. Main results and the role of chance: The women's mean age among groups G1 vs. G2 vs. G3 was, respectively: 39.1±3.5 vs. 38.7±3.3 vs. 37.6±3.8, p < 0.001; the mean KS5 of each group was: 2.9±0.7 vs. 5.4±0.8 vs. 8.0±0.7, p < 0.001 and finally, the euploidy rates comparing the G1 vs. G2 vs. G3 were, respectively: 98/341, 28.7% vs. 124/340, 36.5% vs. 63/121, 52.1%, p < 0.001. A weak correlation between women's age and KIDScore was also observed (-0.173, p < 0.001). Limitations, reasons for caution: Although there is a positive correlation between embryomorphokinetics and euploidy, and the euploidy rate increases with higher KIDscore, only 50% of the high score embryos are euploids. Therefore, it is still important to perform embryo biopsy. Wider implications of the findings: The findings suggest that better embryo morphokinetics provide greater chances of euploidy. Moreover, a weak negative correlation between women's age and KIDScore, possibly due to age-related aneuploidy, was observed. These results highlight time-lapse technology's importance and the future perspective of morphokinetics evaluation improving implantation rates through euploidy identification. Trial registration number: Not Applicable